Modified Bentonite as Sorbent for Removal Tl+ and Bi3+ from Water Samples - JAMSHIDI GOHARI, RASOUL; AFZALI GOROUH, KAVOOS (Asian Journal of Chemistry, 2010)
In present work, modified bentonite sorbent is used for removal of Tl+ and Bi3+ from water samples at trace levels. Modification of bentonite was established with Pd2+ and TiO2 in the solution and solid state. The results showed that TiO2 is proved to be better modifier.